Metabolite-Sensing G Protein Coupled Receptor TGR5 Protects Host From Viral Infection Through Amplifying Type I Interferon Responses - Xiong, Qingqing; Huang, Hongjun; Wang, Ning; Chen, Ruoyu; Chen, Naiyang; Han, Honghui; Wang, Qin; Siwko, Stefan; Liu, Mingyao; Qian, Min; Du, Bing (Frontiers in Immunology, 2018)
The metabolite-sensing G protein–coupled receptors (GPCRs) bind to various metabolites and transmit signals that are important for proper immune and metabolic functions. However, the roles of metabolite-sensing GPCRs in viral infection are not well characterized. Here, we identified metabolite-sensing GPCR TGR5 as an interferon (IFN)-stimulated gene (ISG) which had increased expression following viral infection or IFN-β stimulation in a STAT1-dependent manner. Most importantly, overexpression of TGR5 or treatment with the modified bile acid INT-777 broadly protected host cells from vesicular stomatitis virus (VSV), newcastle disease virus (NDV) and herpes simplex virus type 1 (HSV-1) infection. Furthermore, VSV and HSV-1 replication was increased significantly in Tgr5-deficient macrophages and the VSV distribution in liver, spleen and lungs was increased in Tgr5-deficient mice during VSV infection. Accordingly, Tgr5-deficient mice were much more susceptible to VSV infection than wild-type mice. Mechanistically, TGR5 facilitates type I interferon (IFN-I) production through the AKT/IRF3-signaling pathway, which is crucial in promoting antiviral innate immunity. Taken together, our data reveal a positive feedback loop regulating IRF3 signaling and suggest a potential therapeutic role for metabolite-sensing GPCRs in controlling viral diseases.